Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content:1. A sociological analysis of perceptions of work motivation among young people and its relationship to unemployment: A field study in Ngoussa – AlgeriaMr. Masoudi Abdel Basset, Professor Dr. Bin Issa Muhammad Al Mahdi2. The Effect of Climate on Residential Electrical Energy Consumption in Jeddah CityMs. Khadija Muhammad Samili, Dr. Faida Kamel Boqri3. The Stress System of English Loanwords in Qassimi Arabic: An Optimality Theoretic AnalysisDr. Nuha Naser Alluhaidan4. The Concept of ‘Supernaturalism’ in British and American Fiction: A Comparative StudyMs. Areej Mohammed Mubarak Ali
Keywords: Journal of Human and Social Sciences